Antifungal Activity Test of The Aqueous and Ethanolic Extracts of Strawberry Leaves Against Absidia corymbifera - Trijayanti, Salindri; Handayani, Sri (Indonesian Journal of Chemistry and Environment, 2025)
Absidia corymbifera is an opportunistic fungal pathogen that can cause serious infections, particularly in immunocompromised individuals. However, studies on natural antifungal agents effective against this species remain limited. This study investigates the antifungal activity of strawberry (Fragaria spp.) leaf extracts as a potential natural treatment against A. corymbifera. Aqueous and ethanol extracts were prepared using cold extraction methods—blending and maceration, respectively. Strawberry leaf extract was subjected to a qualitative phytochemical screening test and a quantitative total phenolic content test using the Folin-Ciocalteu method, then an antifungal activity test was carried out using the diffusion method. Phytochemical screening revealed the presence of tannins, flavonoids, and alkaloids in the aqueous extract, while the ethanol extract contained tannins, flavonoids, and steroids. The total phenolic content of ethanol extract of strawberry leaves is greater than that of strawberry leaf aqueous extract. Aqueous and ethanol extracts of strawberry leaves showed fungistatic antifungal inhibition against A. corymbifera with a larger inhibitory zone diameter in strawberry leaf ethanol extract. These findings suggest that strawberry leaf extracts, particularly ethanol-based, hold promise as a natural antifungal agent for controlling infections caused by A. corymbifera.